Determinan Produk Domestik Bruto di Provinsi Bali Tahun 2014-2019 - Desak Ari Gita Wahyuni; Masruri Muchtar; Pardomuan Robinson Sihombing (Future Science, 2023)
This study aims to analyze the components of the Human Development Index on Gross Regional Domestic Product (GRDP) in Bali during the 2014-2019 period. The data used are time series and cross section obtained and processed from the Central Bureau of Statistics. Through a quantitative descriptive approach, this study uses multiple linear regression methods on panel data with the selected estimation model being the Fixed Effect Model. The results showed that the dependent variable of GRDP could be explained by independent variables by 92.03 percent and 7.97 percent of it was influenced by other variables outside this research model. Mean Years School and Life Expectancy variable have a positive effect on GRDP while the Labor Force Participation Rate variable has a negative and insignificant effect on GRDP. Government policies are needed to support equitable distribution of human development in each region